Community perspectives on persistent transmission of lymphatic filariasis in three hotspot districts in Ghana after 15 rounds of mass drug administration: a qualitative assessment - Collins S. K. Ahorlu; Eric Koka; Susan Adu-Amankwah; Joseph Otchere; Dziedzom Komi de Souza (BMC, 2018)
Abstract Background The Global Program for the Elimination of Lymphatic Filariasis (GPELF) started operation in 2000 and aimed at eliminating the disease by the year 2020, following 5-6 rounds of effective annual Mass Drug Administration (MDA). The MDA programme took off in Ghana in 2001 and has interrupted transmission in many areas while it has persisted in some areas after 10 or more rounds of MDA. This study was to appreciate community members' perspectives on MDA after over 15 years of implementation. Findings will inform strategies to mobilise community members to participate fully in MDA to enhance the disease elimination process. Methods This was a qualitative study, employing key-informant in-depth-interviews. Respondents were selected based on their recognition by community members as opinion leaders and persons who were knowledgeable about the topic of interest in the community. A snowball sampling technique was used to select respondents. Results Respondents were well informed about the MDA with most of them saying, it has been implemented for over 12 years. They were aware that the MDA was for the treatment/control of LF (elephantiasis). It came to light that MDA compliance was affected by five related barriers. These are; Medication, Personal, Health system, Disease and Social structure related barriers. Adverse effects of the drugs and the fact that many people perceived that they were not susceptibility to the infection have grossly affected the ingestion of the drugs. Conclusion There is a need for community mobilization and promotional activities to explain the expected adverse reactions associated with the drugs to the people. Also the importance of why every qualified person in the community must comply with MDA must be emphasized.